Media and the methadone drug substitution therapy (MDST): a content analysis of news on methadone In Berita Harian And Harian Metro in 2008 / Siti Hajar Abd Aziz...[et al.] - Abd Aziz, Siti Hajar; Mohd Mothar, Noor Mayudia; Abdul Ghalim, Shahril Anuar (2010)
Malaysia media has been covering the issues of Methadone Drug Substitution Therapy (MDST) since the year 2005, when the government decided to give free syringes, condom and methadone as part of a "harm-reduction" programme for the drug addicts. After a number of years, the public's perception of methadone users and the treatment has not improved much. The public still misconceived the treatment as just another alternative to meet the addiction habits. Question arose whether the media has been supporting the MDST programme in their news based on the style of news writing and the information offered in the news. Therefore, the paper will examine the contents and writing style of news on methadone treatment by Berita Harian and Harian Metro in throughout year 2008 to determine their level of support on the programme. The study found out that Berita Harian was dedicated at focusing their news on methadone to on the awareness and the treatment part of the methadone maintenance, using sources from ministry and health practitioners. Harian Metro, however, preferred to represent methadone in the form of crime news, and using enforcement bodies as their sources. Although both newspapers has shown their support to the methadone treatment programme, but methadone treatment did suffered from this stereotype of news values practised by most tabloid newspapers when it often fall under the theme of crime. It was feared that associating methadone with crime and harmful drugs would create a perception that methadone is just another type of harmful drugs and not a therapy drug or medicine for the addicts.